PENCATATAN AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH: PADA UMKM KERIPIK SAMBAL SIBOLGA - Khairani Alawiyah Matondang; Titian Dhea Fresensia Purba; Kesia Septina Putri Tarigan; Alexa Angelica Br Nababan; Jessica Br Simanungkalit (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
Accounting is information that processes transaction data and economic activities into useful financial information for parties to evaluate the performance and economic condition of a business. This research was conducted to determine the extent of the implementation of accounting record-keeping practices in MSMEs (Micro, Small, and Medium Enterprises) to support accurate economic activities, even within the scope of micro businesses. The sample for this study was taken from a type of MSME in the snack food industry, namely KERIPIK SAMBAL SI BOLGA. This research uses a descriptive qualitative method, collecting primary and secondary data through unstructured interviews via WhatsApp with the owner of the Kripik Sibolga business. The results of the study, based on the conducted research and discussion, show that the MSME KERIPIK SAMBAL SIBOLGA still performs accounting record-keeping in a very simple manner, as is common among MSMEs, where records are only made during sales transactions and are noted in a receipt book.